ChemInform Abstract: Garratt—Braverman Cyclization on Basic Alumina: A Green Protocol with Improved Selectivity. Issue 52 (29th December 2014) - Ghosh, Debaki; Biswas, Subhanip; Ghosh, Koena; Basak, Amit
Abstract Aryl‐ and hetaryl‐substituted bispropargyl substrates pre‐absorbed on basic alumina undergo Garratt—Braverman cyclization to afford aryl naphthalene derivatives and related compounds.